Public Debt and Growth - Woo, Jaejoon (IMF Working Papers; Working Paper ;, 2010)
This paper explores the impact of high public debt on long-run economic growth. The analysis, based on a panel of advanced and emerging economies over almost four decades, takes into account a broad range of determinants of growth as well as various estimation issues including reverse causality and endogeneity. In addition, threshold effects, nonlinearities, and differences between advanced and emerging market economies are examined. The empirical results suggest an inverse relationship between initial debt and subsequent growth, controlling for other determinants of growth: on average, a 10 percentage point increase in the initial debt-to-GDP ratio is associated with a slowdown in annual real per capita GDP growth of around 0.2 percentage points per year, with the impact being somewhat smaller in advanced economies. There is some evidence of nonlinearity with higher levels of initial debt having a proportionately larger negative effect on subsequent growth. Analysis of the components of growth suggests that the adverse effect largely reflects a slowdown in labor productivity growth mainly due to reduced investment and slower growth of capital stock.